Professional Ethics of Judges in Court - Fahira, Meida Anggi; Fahmi, Syawaludin Nur A. (MILRev: Metro Islamic Law Review, 2022)
The discourse of thought departs from the reality of law enforcers (especially judges) who ignore moral values. Even though professional actors (judges) already have a professional code of ethics as a moral standard, it has not had a positive impact, especially not being able to change society's negative image of faces. One way to uphold the rule of law is by maintaining ethics, professionalism, and discipline. The code of ethics for the profession of judges in principle contains moral values that underlie professional personality, namely freedom, justice, and honesty.